Goblet Cells and Mucin Related Gene Expression in Mice Infected with Eimeria papillata. (3rd December 2013) - Dkhil, Mohamed A.; Delic, Denis; Al-Quraishy, Saleh
Abstract : Coccidiosis causes considerable economic loss in the poultry industry. The current study aimed to investigate the response of goblet cells as well as the induced tissue damage during Eimeria papillata infection. Mice were infected with sporulated E. papillata oocytes. On day 5 postinfection, the fecal output was determined. Also, the jejunum was prepared for the histological, histochemical, and molecular studies. Our results revealed that the intestinal coccidian infection with E. papillata induced a marked goblet cell hypoplasia and depleted mucus secretion. Also, the infection was able to alter the jejunal architecture and increased the apoptotic cells inside the villi. In addition, the real-time PCR results indicated that the inflammatory cytokines: TNF- α, iNOS, IFN- γ, and IL-1 β, were significantly upregulated. In contrast, the mRNA expression patterns of IL-6 in response to E. papillata infection did not differ significantly between control and infected mice. Moreover, the mRNA expression of TLR4 was significantly upregulated, whereas the expression of MUC2 is significantly downregulated upon infection. Further studies are required to understand the regulatory mechanisms of goblet cells related genes.